Cogan's Syndrome Associated with Orbital Inflammation. (June 2013) - Shahid, Fatema Lucy; Mukherjee, Rita; Knapp, Christopher
Abstract Cogan's syndrome is a relatively rare inflammatory disorder presenting with a combination of ocular and vestibuloauditory symptoms. The first cases were described by David Cogan in 1945. Typically the ocular signs involve the anterior segment; however there are no descriptions of orbital inflammation associated with Cogan's syndrome. We describe such a case. A 66-year-old immunosuppressed male patient with known Cogan's syndrome presented to the eye department with right-sided proptosis, chemosis and ocular injection. Ocular motility was reduced. Other than Cogan's syndrome there were no other systemic disorders. Medical treatment included: Azathioprine 125 mg/day and low dose Tab Prednisolone 30 mg/day. A provisional diagnosis of orbital cellulitis was made and intravenous antibiotics started. Blood investigations showed raised CRP levels 475 mg/L and raised WCC (24 × 109/l). An urgent CT scan of the head and orbits ruled out orbital cellulititis. The diagnosis was revised and the patient was treated for orbital inflammatory disease. Pulsed intravenous methlyprednisolone was commenced and oral steroids were increased to 60 mg/day, the Azathioprine was continued. Over the following week, the proptosis had resolved, and oral steroids were reduced back to the maintenance dose. To our knowledge this is the first description of orbital inflammatory disease associated with Cogan's syndrome.